THE INFLUENCE OF THE EDUCAPLAY-BASED GAME BASED LEARNING MODEL ON THE LEARNING OUTCOMES OF CLASS X STUDENTS IN GEOGRAPHY LEARNING AT SMA NEGERI 3 BIREUEN - nuriska salsabila; Rahmi Novalita; Hariki Fitrah (Fakultas Keguruan Dan Ilmu Pendidikan Universaitas PGRI Banyuwangi, 2026)
This study aimed to determine the effect of the Educaplay-based Game Based Learning model on the learning outcomes of class X students in geography learning on seismic material at SMA Negeri 3 Bireuen. This research employed a quantitative approach with a One Group Pretest-Posttest Design involving 33 students selected through total sampling. Data were collected through multiple-choice tests administered before and after treatment and analyzed using descriptive statistics, paired sample t-test, effect size analysis, and N-Gain analysis. The results showed a significant difference between pretest and posttest scores (p < 0.05). The mean score increased from 57.27 in the pretest to 60.61 in the posttest. Effect size analysis indicated a large effect, suggesting that the learning model had a strong influence on students' learning outcomes. However, the average N-Gain score of 0.0732 was categorized as low. Therefore, it can be concluded that the Educaplay-based Game Based Learning model significantly affects students' learning outcomes, although further development is needed to optimize learning improvement.